Transformational leadership and its impact on performance at work, field study in the football sports league of the province of M’sila - عمرون مفتاح; زاوي زيد (sports creativity, 2025)
Abstract : This study aimed to identify the effect of transformational leadership on the performance of the employees of the sports league of the M'sila wilaya, using the descriptive approach that fits the subject of the study. The researcher used the questionnaire that applied it to a sample of 41 employees of the sports league of the wilaya of M'sila. The results obtained after the study of transformational leadership and its impact on work performance, as well as the application of appropriate statistical methods and by reading, analyzing and interpreting the tables, the results of our study are as follows: In terms of the impact of transformational leadership on job performance, the researcher concluded that transformational leadership has an effect on job performance, that is, that it has the characteristics of a transformational leader, including positive influence, inspiring motivation, and individual consideration, then, subordinates possessed creative abilities and abilities. The researcher shows with this result that the leader who possesses the attributes of the transformational leader contributes greatly to the development of the capacities of the subordinates of the workers of the footbal sports league of the wilaya of M'sila